HIGH-PRECISION BAYESIAN CHRONOLOGICAL MODELING ON A CALIBRATION PLATEAU: THE NIEDERTIEFENBACH GALLERY GRAVE. Issue 5 (7th October 2020) - Meadows, John; Rinne, Christoph; Immel, Alexander; Fuchs, Katharina; Krause-Kyora, Ben; Drummer, Clara
ABSTRACT: We combine the results of a radiocarbon ( 14 C) dating program with archaeogenetic, osteological and sparse stratigraphic data, to construct a Bayesian chronological model for a multi-generational sequence situated entirely on a plateau in the 14 C calibration curve. Calibrated dates of individual human bones from the Late Neolithic gallery grave at Niedertiefenbach, Hesse, Germany, span the entire calibration plateau in the late 4th millennium (ca. 3350–3100/3000 cal BC), but our model restricts the overall period of burial to 3–6 generations centered on the later 3200s, and provides narrower absolute date ranges for specific individuals and associated events. We confirm the accuracy and robustness of this model by sensitivity tests of each of its components. Beyond providing a more dynamic narrative for the formation of the heterogenous burial population at Niedertiefenbach, our results show that calibration plateaus are suitable periods for Bayesian chronological modeling of even relatively brief sequences, provided that all the information employed is correct. Prior information constraining both the order of events, and of potential date differences between them, is essential for the model to give accurate, unimodal estimates of the dates of these events.